Investigation of thermal comfort properties of zinc oxide coated woven cotton fabric - ŞİMŞEK, RAMAZAN (TAYLOR & FRANCIS LTD, 2017)
In this paper, we investigated thermal comfort properties of twill weave cotton woven fabric coated zinc oxide layer in Roaches high temperature sample dyeing machine in gentle conditions. The effect of coated film structure on thermal comfort properties of the fabric was characterized using SEM observation, EDS analysis, and Permetest instruments. EDS analysis and SEM images of the ZnO coated twill weave cotton fabric proved that ZnO coating layer which has significant effects on thermal comfort properties was successfully synthesized on the fabric surface by covering the pores of the twill weave cotton fabric. Results showed that thermal resistance of ZnO coated fabric increased approx. 36-52%, while thermal conductivity is decreased approx. 27-34% and WVP is decreased approx. 22-28%. Further studies have started and in progress to evaluate wash fastness, wear performance, abrasion properties, and fabric handle properties.
Keywords: Zinc oxide; coating; thermal comfort; cotton fabric; SONOCHEMICAL APPROACH; ZNO; PARTICLES